Topological Indices of Families of Bistar and Corona Product of Graphs - A. Khalid; N. Kausar; M. Munir; M. Gulistan; M. M. Al-Shamiri; T. Lamoudan (Journal of Mathematics)
Topological indices are graph invariants that are used to correlate the physicochemical properties of a chemical compound with its (molecular) graph. In this study, we study certain degree-based topological indices such as Randić index, Zagreb indices, multiplicative Zagreb indices, Narumi–Katayama index, atom-bond connectivity index, augmented Zagreb index, geometric-arithmetic index, harmonic index, and sum-connectivity index for the bistar graphs and the corona product KmoKn′, where Kn′ represents the complement of complete graph Kn.